HUBUNGAN TINGKAT STRES DENGAN KUALITAS TIDUR PADA PASIEN DIABETES MELLITUS TIPE II DI RS BHAYANGKARA MANADO - Ariska, Ariska; Lanawaang, Nathasya G. (Yayasan Syalom Cipta Sumikolah, 2024)
Background: Diabetes mellitus (DM) is a non-communicable disease which is still a problem. Stress is a natural and very important part of life, but if it lasts too long and is severe it can damage human health. Based on the results of this preliminary research, researchers are interested in conducting research which aims to analyze the relationship between stress levels and sleep quality in type II diabetes mellitus patients at Bhayangkara Hospital, Manado. Objective: To determine the relationship between stress levels and sleep quality in type II diabetes mellitus patients. Methodology: This research uses quantitative methods with a cross-sectional approach. The population in this study was Bhayangkara Manado Hospital, totaling 54 people into 35 samples with a sampling technique using purposive sampling technique. The research was carried out by conducting a relationship between stress levels and sleep quality in diabetes mellitus patients, using the chi-square test to obtain a value of ρ-value = 0.000 which is smaller than the value of α = 0.05. This means that H0 is rejected, so there is a relationship between stress levels and quality. Sleep in Type 2 Diabetes Mellitus Patients at Bhayangkara Hospital Manado.